2017
DOI: 10.4103/2249-4863.214967
|View full text |Cite
|
Sign up to set email alerts
|

Socio-clinical profile of married women with history of induced abortion: A community-based cross-sectional study in a rural area

Abstract: Background:Induced abortion contributes significantly to maternal mortality in developing countries yet women still seek repeat induced abortion in spite of the availability of contraceptive services.Objectives:(1) To study the sociodemographic profile of abortion seekers. (2) To study the reasons for procuring abortions by married women of reproductive age group.Materials and Methods:It was a cross-sectional community-based study. All the married women of reproductive age group (15–49 years) with a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this study, approximately 43.4% of participants underwent repeat abortions. Although this prevalence is significantly lower than the 65.2% reported in 2013,27 it remains notably higher than that among abortion seekers in some other countries or regions, such as Sweden (25.8%),28 southwestern Ontario (23.1%)29 and India (24.2%) 30. While we found that women receiving high-quality PAC services had a lower risk, specifically those served in PAC exemplary units, women living in medium-GDP areas still faced a higher risk of repeat abortion.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this study, approximately 43.4% of participants underwent repeat abortions. Although this prevalence is significantly lower than the 65.2% reported in 2013,27 it remains notably higher than that among abortion seekers in some other countries or regions, such as Sweden (25.8%),28 southwestern Ontario (23.1%)29 and India (24.2%) 30. While we found that women receiving high-quality PAC services had a lower risk, specifically those served in PAC exemplary units, women living in medium-GDP areas still faced a higher risk of repeat abortion.…”
Section: Discussionmentioning
confidence: 65%
“…Although this prevalence is significantly lower than the 65.2% reported in 2013, 27 it remains notably higher than that among abortion seekers in some other countries or regions, such as Sweden (25.8%), 28 southwestern Ontario (23.1%) 29 and India (24.2%). 30…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Pattainaik et al it was found out that among the various reasons given by patients for undergoing an abortion, the most common reason was found to be poverty accounting about 39.4% and 17.2% of cases were due to gender based preferences. 9 Another study by Shivakumar and Vishvanath, an unplanned pregnancy (30.7%) followed by contraceptive failure (29.3%) were amongst the commonest reasons. 10 One study by Bahadur et al cited termination of unplanned pregnancy (32.8%) as the most common reason, poverty in 24.6%, contraceptive failure in 22.3% and completed family in 20.3% of women.…”
Section: Discussionmentioning
confidence: 97%
“…Usually, data on MMA or a significant survey of public and private health facilities is used to estimate abortion rate (5,6,8). Desire to limit family size, birth spacing, son preference, medical reasons, poverty, violence and belief system are major factors of abortion (10,11,12). In this study, some other potential factors of abortion such as women's age, place of residence and educational level, wealth index, religion, ecological zone, caste, marital status, use of modern contraceptives, media exposure and knowledge of fertile period are explored.…”
Section: Introductionmentioning
confidence: 99%